A Review of Risk Factors for Methamphetamine-Related Psychiatric Symptoms - Chang, Xiangwen; Sun, Yan; Zhang, Yang; Muhai, Jiana; Lu, Lin; Shi, Jie (Frontiers in Psychiatry, 2018)
The illegal use of methamphetamine (MA) is a growing public health concern globally and results in a series of negative effects. The prominent detrimental effect of MA use is MA-related psychiatric symptoms (MAP) and is observed at a much higher incidence compared to the general population. MAP often includes multiple dimensions of cognitive impairment and induces adverse consequences such as, violence and suicide. However, the assessment methods for MAP are not standardized. Hence, it is necessary to investigate factors that affect the progression of psychiatric symptoms in individuals who use MA. A review of published studies was performed by searching the following databases: PubMed, EMBASE, and PsycINFO from inception to 31 May, 2018. The search strategy included methamphetamine, dependence, psychiatric symptoms, and risk factor terms. We reviewed the different features of MAP and the various types of assessment instruments and summarized MAP risk factors from MA use-related factors, socio-demographic characteristics, life events, and genetic factors. We found that MAP was consistently and causally associated with MA use, particularly as it relates to the frequency and amount of MA use. Other MAP-related risk factors like life events and genetics were relatively inconsistent in their association with MAP. Hence, causal and longitudinal studies that focus on multilateral comparisons are required. This review provides high quality evidence for MAP risk factors and would be helpful for developing early prevention and treatment strategies for MAP.